2004
DOI: 10.1089/107555304322849039
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Effects of Music, Noise, and Healing Energy Using a Seed Germination Bioassay

Abstract: Objective: To measure biologic effects of music, noise, and healing energy without human preferences or placebo effects using seed germination as an objective biomarker.Methods: A series of five experiments were performed utilizing okra and zucchini seeds germinated in acoustically shielded, thermally insulated, dark, humid growth chambers. Conditions compared were an untreated control, musical sound, pink noise, and healing energy. Healing energy was administered for 15-20 minutes every 12 hours with the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 19 publications
6
57
0
20
Order By: Relevance
“…A study conducted on the effect of music with low frequencies on the germination rate has revealed that music with low frequencies increased germination rate (Creath and Schwartz, 2004). Further, the soft rhythm of music and sounds have influenced plants to grow healthier (Chowdhury and Gupta, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on the effect of music with low frequencies on the germination rate has revealed that music with low frequencies increased germination rate (Creath and Schwartz, 2004). Further, the soft rhythm of music and sounds have influenced plants to grow healthier (Chowdhury and Gupta, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that sound vibration can be used to stimulate a seed or plant [2]. Previous studies indicate that musical sound has a significant effect on the number of seeds sprouted compared to noise and untreated control and sound vibrations directly affect living biologic systems [1]. Foliage planted along freeways to reduce noise pollution often grows differently than foliage planter in a quiet environment [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sound is known to affect the growth of plants [1]. Studies have also shown that sound vibration can be used to stimulate a seed or plant [2].…”
Section: Introductionmentioning
confidence: 99%
“…Different metabolic activities including enzyme activation and hormonal changes occur during seed germination, and sound is known to directly affect biological systems including those involved in seed germination. Creath and Schwartz (2004) compared effects of music, noise, and healing energy using seed germination assay. Musical sound has been shown to significantly enhance the sprouting of okra and zucchini seeds than the noise effect.…”
Section: Role Of Sound Waves On Plant Growth and Developmentmentioning
confidence: 99%